Affordances as a Means to Assess Human-Sensor-Robot Performance. (September 2016) - Murphy, Taylor B.; Morison, Alexander
Tele-operated sensor-robot systems consist of sensors on a robotic platform present in some location with a human operator located somewhere outside the scene of interest. One common theme from observing operators of these systems in the field is that they must explicitly deliberate on the fit between a robot's capabilities and the surrounding environment. Even simple tasks like moving through an aperture or reaching for an object present a challenge. In perceptual psychology the fit between capability and environment is called an affordance (Gibson, 1986). The theory of affordances provides a way to frame the difficulty robot operators have with teleoperation. From this perspective, the design of many robotic platforms appears to hobble an operator's natural ability to perceive affordances, impairing task performance (Morison, Woods & Murphy, 2014). This insight about the source of operator difficulty suggests that assessing the performance of any robotic system must also measure the ability of the operator to perceive affordances in the remote environment. The authors developed a method to measure the perceptual performance of a robot operator judging the reachability of an object. The method includes a software simulation of a robotic platform, including a robotic arm, and its environment. People acting as Robot Handlers (Woods et al., 2004) make reachability judgments from images captured by the robot's camera. This method can generalize to assess the ability of any human-sensor-robot system to perceive other affordances. The measurement procedure is built on well-established methods developed in perceptual psychology (Warren, 1987; Heft 1993). The procedure uses a within subjects, repeated measures design. Target objects are presented at different distances from the robot, and participants are asked to judge the reachability of the object. The placement of the target object is based on a staircase sampling algorithm that adapts to the participant's performance (Garcia-Perez, 2001). The sampling resulted in estimates for two different points on a psychometric function for each participating judge. The position and distance between these two points is a measure of the accuracy and precision of the participant's ability to perceive the reachability affordance. The measurement procedure tests the impact of different visual cues available when the view into a remote environment is mediated by a sensor platform. The first test of the method, reported here, used three different environments that share attributes with real world operating environments. For example, the low condition was similar to operating underwater with no ground plane or shadows present. The other two conditions, medium and high, approximate the visual cues available when operating in a deconstructed environment, like a collapsed building, and in a constructed environment, respectively. The results from the method were psychophysical functions for the human-sensor-robot system, where performance was directly proportional to the number of visual cues to depth. Interestingly, judgements of reachability based on sensor feeds from a robotic platform are poorer than making the same judgment when directly viewing the target and scene as in classic studies of reachability perception (Warren, 1987). The average distance between the two estimated points for the high condition was slightly below half the robot arm's length (44%). And for the low condition this width increased to nearly the entire length of the robot arm (84%). In conclusion, the results show two important points. First, it is possible to perform a psychophysical assessment of an affordance for an operator whose perception is mediated by a robotic system. And second, the limited ability of participants to perceive reachability corroborates observations of operators having difficulty tele-operating robotic platforms. The test is the first in a planned series that will continue to refine the method for human-sensor-robot system assessment. Additionally future studies will adapt this method to compare different sensor platform designs to assess whether sensor platform design can systematically alter the ability of robot handlers to perceive affordances in the remote environment.